Proteome Analysis of various types of Panax ginseng using 2-Dimensional Electrophoresis - Jong-Sung,We; Hee-Soo,Park; Ki RoK,Kwon (Korean Pharmacopuncture Institute, 2007)
Objectives : The purpose of this study was to obtain an objective differentiating method for various types of Panax ginseng: ginseng, cultivated wild ginseng, and natural wild ginseng which are distinctive according to their growing environment. Methods : The roots, stem, and leaves of several types of ginseng were collected and comparative analysis of proteome was conducted on each part using 2-DE and the results examined. Results : 1. Proteome images of the respective parts within the samples showed spot-matching in most cases, suggesting that they are genetically identical panax ginseng. 2. Similar distribution patters were seen within the different parts of the Panax ginseng: ginseng, Chinese cultivated wild ginseng, and the 5 and 10 years old Korean cultivated wild ginseng. 3. For a quantitative evaluation of spots showing differences among the samples, 102 spots from the roots, 109 spots from the stems, and 132 spots form the leaves which showed a difference were selected and centrifugal identification was conducted. 4. Peculiar proteins from each respective part of the Panax ginseng were identified and the top 20 spots with significant differences were selected and analyzed in order to provide a differentiation rate among the samples. The accuracy rate ranged between 23.0-38.8%. 5. Differentiation rate of the top 10 spots with significant differences showed a 50-85% accuracy rate, and the differentiation rate was especially high for the stem of Chinese cultivated wild ginseng and Korean cultivated wild ginseng.